The Value of Restaging With Chest and Abdominal CT/MRI Scan After Neoadjuvant Chemoradiotherapy for Locally Advanced Rectal Cancer. Issue 47 (November 2015) - Liu, Guo-Chen; Zhang, Xu; Xie, E.; An, Xin; Cai, Pei-Qiang; Zhu, Ying; Tang, Jing-Hua; Kong, Ling-Heng; Lin, Jun-Zhong; Pan, Zhi-Zhong; Ding, Pei-Rong
Abstract : Abstract: Little was known with regard to the value of preoperative systemic restaging for patients with locally advanced rectal cancer (LARC) treated with neoadjuvant chemoradiotherapy (CRT). This study was designed to evaluate the role of chest and abdominal computed tomography (CT) scan or magnetic resonance imaging (MRI) on preoperative restaging in LARC after neoadjuvant CRT and to assess the impact on treatment strategy. Between January 2007 and April 2013, 386 newly diagnosed consecutive patients with LARC who underwent neoadjuvant CRT and received restaging with chest and abdominal CT/MRI scan were included. Imaging results before and after CRT were analyzed. Twelve patients (3.1%) (6 liver lesions, 2 peritoneal lesions, 2 distant lymph node lesions, 1 lung lesions, 1 liver and lung lesions) were diagnosed as suspicious metastases on the restaging scan after radiotherapy. Seven patients (1.8%) were confirmed as metastases by pathology or long-term follow-up. The treatment strategy was changed in 5 of the 12 patients as a result of restaging CT/MRI findings. Another 10 patients (2.6%) who present with normal restaging imaging findings were diagnosed as metastases intra-operatively. The sensitivity, specificity accuracy, negative predictive value, and positive predictive values of restaging CT/MRI was 41.4%, 98.6%, 58.3%, and 97.3%, respectively. The low incidence of metastases and minimal consequences for the treatment plan question the clinical value of routine restaging of chest and abdomen after neoadjuvant CRT. Based on this study, a routine restaging CT/MRI of chest and abdomen in patients with rectal cancer after neoadjuvant CRT is not advocated, carcino-embryonic antigen (CEA) -guided CT/MRI restaging might be an alternative.